Proceedings of the 2008 Symposium on Eye Tracking Research &Amp; Applications - ETRA '08 2008
DOI: 10.1145/1344471.1344518
|View full text |Cite
|
Sign up to set email alerts
|

A robust 3D eye gaze tracking system using noise reduction

Abstract: This paper describes a novel real-time 3D gaze estimation system. The system consists of two cameras and two IR light sources. There are three novelties in this method. First, in our system, two IR lights are mounted near the centers of the stereo cameras, respectively. Based on this specific configuration, the 3D position of the corneal center can be simply derived by the 3D reconstruction technique. Then, after extracting the 3D position of the "virtual pupil" correctly, the optical axis of the eye can be ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…In these set-ups the internal camera parameters such as the focal length are known, as well as the position and orientation of the cameras and light sources. Other researchers have proposed similar 3D methods to compute the optical axis of the eye from the pupil center and corneal reflections (e.g [15], see [13] for an overview of the different approaches). Alternative methods have been proposed that estimate the optical axis from the shape of the limbus [16], ellipse descriptions of the pupil contour combined with conic algebra [17], or corneal reflections and pupil center combined with pupil-contour data [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these set-ups the internal camera parameters such as the focal length are known, as well as the position and orientation of the cameras and light sources. Other researchers have proposed similar 3D methods to compute the optical axis of the eye from the pupil center and corneal reflections (e.g [15], see [13] for an overview of the different approaches). Alternative methods have been proposed that estimate the optical axis from the shape of the limbus [16], ellipse descriptions of the pupil contour combined with conic algebra [17], or corneal reflections and pupil center combined with pupil-contour data [18].…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is assumed that the entrance pupil lies in front of the actual pupil, that the entrance pupil is slightly larger, and that the optical axis goes through the center of the actual pupil and the entrance pupil. Chen et al investigated this assumption through ray-tracing for a stereocamera set-up and found small deviations of the virtual pupil, with a resulting error in simulated gaze estimates of 0.08 degrees on average [15]. However, they applied a simplified geometrical model of the eye, in which the cornea was modelled as a convex sphere with only one refractive surface.…”
Section: Introductionmentioning
confidence: 99%
“…To compare our method to the method that uses a spherical model of the cornea, we also calculated the POG by using Chen's method [11] at the same time. Chen's method uses a spherical model of the cornea and the same arrangement of cameras and light sources as our system.…”
Section: Methodsmentioning
confidence: 99%
“…It passes through C j and intersects the camera image plane at a point P j j . If the cornea is perfectly spherical, the line connecting L j and P j j would pass through A, and the position of A can be easily determined using two cameras as described in Chen's method [11]. However, the position of A cannot be accurately estimated when light is reflected from around an edge of the surface of the cornea.…”
Section: Estimation Of the Optical Axis Of The Eyementioning
confidence: 99%
See 1 more Smart Citation